'Swinging on the anchor': The difficulties in achieving greenhouse gas abatement in shipping via virtual arrival. (August 2019) - Poulsen, René Taudal; Sampson, Helen
Highlights: We study efficiency measures for greenhouse gas emission abatement in shipping. We explain why ships wait at anchor and why virtual arrival is uncommon. We show how cargo-owners' decisions increase emissions from shipping. We show that commercial priorities outweigh fuel saving benefits of virtual arrival. We describe how virtual arrival systems may increase seafarer fatigue. Abstract: The abatement of greenhouse gas emissions represents a major global challenge and an important topic for transportation research. Several studies have argued that energy efficiency measures for virtual arrival and associated reduced anchorage time can significantly reduce emissions from ships by allowing for speed reduction on passage. However, virtual arrival is uncommon in shipping. In this paper, we examine the causes for waiting time for ships at anchor and the limited uptake of virtual arrival. We show the difficulties associated with the implementation of virtual arrival and explain why shipping is unlikely to achieve the related abatement potential as assumed by previous studies. Combining onboard observations with seafarers and interviews with both sea-staff and shore-based operational personnel we show how charterers' commercial priorities outweigh the fuel saving benefits associated with virtual arrival. Moreover, we demonstrate how virtual arrival systems have unintended, negative consequences for seafarers in the form of fatigue. Our findings have implications for the IMO's greenhouse gas abatement goals.